Out of the vacuum: The effect of tax liability changes on compliance in the presence of withholding position and group affiliation - Austin, Chelsea Rae; Schmitt, Donna Bobek; Seifert, Spenser G. (Contemporary Accounting Research, 2025)
Abstract Prior research has established that tax liability increases lead to decreased compliance. However, tax liability changes do not happen in a vacuum. Notably, prior research has also identified a withholding phenomenon: individuals in a tax due position are less compliant than those in a refund position. Additionally, tax law changes are often enacted in politically polarized environments. We examine how three factors—tax liability changes, withholding position, and group affiliation—combine to influence individuals' tax compliance decisions. Our experimental results show that a tax increase is universally experienced as a loss, even when coupled with a tax refund and enacted by an ingroup, leading to decreased compliance. However, a tax decrease coupled with a tax due position is viewed neutrally and leads to less compliance than a tax decrease coupled with a tax refund. Further, group affiliation influences compliance in some situations. Individuals in a tax due position are less compliant when an outgroup, versus an ingroup, is responsible for the tax change. This study contributes to the mental accounting literature by examining how individuals react to mixed gain/loss situations when the gains and losses are of different types. We also integrate the previous separate research streams on the withholding phenomenon and tax liability changes. Practically, our results contribute to tax policy by showing how individuals react when tax law changes are enacted. Importantly, even when a tax change results in a decrease in tax liability, tax compliance may be affected by individuals' withholding position and group affiliation.